2013
DOI: 10.1007/10_2013_179
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Understanding of Agrobacterium rhizogenes-Derived Genes and Their Effects on Stress Resistance and Plant Metabolism

Abstract: It is commonly accepted that the plant pathogens Agrobacterium rhizogenes and Agrobacterium tumefaciens, acting via their T-DNA oncogenes, disturb hormone metabolism or hormone perception pathways in plants, thereby attaining their aim of successful pathogenesis. In this work, we summarize recent data on the A. rhizogenes rolC and rolB oncogenes in comparison to the A. tumefaciens 6b oncogene with respect to their effects on the physiology of transformed cells. The newly discovered functions of the rol genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 65 publications
2
30
0
3
Order By: Relevance
“…These oncogenes cause a pleiotropic effect on plant growth and development and affect defense reactions and secondary metabolism. Agrobacterium rhizogenes and A. tumefaciens T-DNA oncogenes (rolA, rolB, rolC and 6b) effectively modulate biosynthesis of secondary metabolites (Bulgakov et al 2013). The 6b oncoprotein of A. tumefaciens targets key components of the miRNA processing machinery, and specific 6b/SE and 6b/ AGO1 interactions have been revealed , resulting in decreased levels of miR162, miR164, miR319 and miR165/166 in 6b overexpressing plants .…”
Section: Regulation Of Plant Secondary Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…These oncogenes cause a pleiotropic effect on plant growth and development and affect defense reactions and secondary metabolism. Agrobacterium rhizogenes and A. tumefaciens T-DNA oncogenes (rolA, rolB, rolC and 6b) effectively modulate biosynthesis of secondary metabolites (Bulgakov et al 2013). The 6b oncoprotein of A. tumefaciens targets key components of the miRNA processing machinery, and specific 6b/SE and 6b/ AGO1 interactions have been revealed , resulting in decreased levels of miR162, miR164, miR319 and miR165/166 in 6b overexpressing plants .…”
Section: Regulation Of Plant Secondary Metabolismmentioning
confidence: 99%
“…Moreover, these cultures would potentially become more resistant to stresses and pathogens. This principle was partially realized in rolC-or rolB-expressing plant cells, which were resistant to stresses and produced high levels of secondary metabolites for many years (Bulgakov et al 2013). Because certain miRNAs modulate both growth and secondary metabolism, the establishment of plant cell cultures that combine vigorous growth with high production ability is a highly attractive goal (a ''dream'' of plant biotechnologists).…”
Section: Artificial Mirnas (Amirnas)mentioning
confidence: 99%
“…ORF13 ) to generate meristem-like cells that can later differentiate into various types of organ-specifi c cells [ 90 -92 ]. The mechanism by which rol genes orchestrate both cell differentiation and secondary metabolism is still unknown, but it seems the increased secondary metabolism is due to the activity of some rol B activated-transcription factors that inhibit repressors of secondary metabolism which plant cells normally use to promote metabolic homeostasis [ 88 ]. HbEREBP1 and CrTF12 transcription factors, respectively.…”
Section: Manipulation Of Mechanisms Governing Cell Differentiation Inmentioning
confidence: 99%
“…Bulgakov [9] reviewed the functions of rol genes in plant secondary metabolism and suggested that rol genes are potential activators of secondary metabolism in transformed cells of wide range of species and may be used as a powerful tool to manipulate secondary metabolites in cultured plant cells. The extent of secondary metabolism activation varies among plant species from 2-to 300-fold depending on the group of secondary metabolites and the plant species [10].…”
Section: Introductionmentioning
confidence: 99%